Thermal and mechanical behaviour of sisal/phenolic composites - Milanese, Andressa Cecilia [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier B.V., 2012)
This research proposes the development of polymeric composites reinforced with natural fibres to become stronger the damaged timber structures and proposes thermal and mechanical characterization of these composites. Fibres with larger structural applications are glass and carbon fibres but the use of natural fibres is an economical alternative and possesses many advantages such as biodegradability, low cost and is a renewable source. Woven sisal fabric was submitted to heat treatment before moulding and the influence of moisture content of fibres on the composites behaviour was observed. The paper presents mechanical characterization by tensile and flexural strength of woven sisal fabric composites, with and without thermal treatment (at 60 degrees C for 72 h) on the fabric, thermal characterization by TGA and the manufacturing process by compression moulding. Experimental results show to sisal/phenolic composites a tensile strength and a flexural strength value of 25.0 MPa and 11.0 MPa, respectively, independent to the use of sisal fibres with or without thermal treatment. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Mechanical properties; Thermal properties; Sisal fabrics/textiles; Compression moulding; Natural fibre composites